2021
DOI: 10.3390/cells10051028
|View full text |Cite
|
Sign up to set email alerts
|

Positive Correlation between nNOS and Stress-Activated Bowel Motility Is Confirmed by In Vivo HiBiT System

Abstract: Neuronal nitric oxide synthase (nNOS) has various roles as a neurotransmitter. However, studies to date have produced insufficient data to fully support the correlation between nNOS and bowel motility. This study aimed to investigate the correlation between nNOS expression and gastrointestinal (GI) tract motility using a stress-induced neonatal maternal separation (NMS) mouse model. In this study, we generated a genetically modified mouse with the HiBiT sequence knock-in into the nNOS gene using CRISPR/Cas9 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…The increased nNOS suggested the presence of more Cajal cells in CACS mice. Other studies have also shown that nNOS is positively correlated with irritable bowel motility (Han et al, 2021). However, SNAP treatment had no significant effect Schematic of this study.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The increased nNOS suggested the presence of more Cajal cells in CACS mice. Other studies have also shown that nNOS is positively correlated with irritable bowel motility (Han et al, 2021). However, SNAP treatment had no significant effect Schematic of this study.…”
Section: Discussioncontrasting
confidence: 79%
“…The increased nNOS suggested the presence of more Cajal cells in CACS mice. Other studies have also shown that nNOS is positively correlated with irritable bowel motility ( Han et al, 2021 ). However, SNAP treatment had no significant effect on the expression of 5-HT or nNOS in CACS mice, which implied that neither 5-HT nor nNOS might be the mediator through which the LHA鈥揃LA MCHergic neural pathway acts on the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 89%
“…The NO plays an important role in the regulation of intestinal motility. The formation of reactive oxygen species would produce an alteration in the NO bioavailability, leading to alterations in the intestinal motility [43,44,46,47]. This study showed that H. stoechas extract inhibit the content of MDA+4-HDA produced in the tissue treated with LPS, demonstrating the antioxidant activity of the H. stoechas extract.…”
Section: Mda+4-hda Contentmentioning
confidence: 55%
“…In addition, it was reported that a high expression level of nNOS in the brain and colon of IBS rats, whereas a positive correlation was found between nNOS expression and bowel motility in stress-induced IBS rats. [20]. Clinical studies have also reported increased NO production in plasma and rectal tissues of IBS patients [21,22].Collectively, these ndings suggest that the gut microbiota and nNOS are likely key factors regulating stress-induced IBS with visceral hypersentivity.…”
Section: Introductionmentioning
confidence: 76%
“…Previous studies have shown that nNOS is a key enzyme for the production of NO in central and peripheral nervous systems [40]. Han et al reported a signi cant increase in nNOS expression in organs of the large intestine, adrenal gland, and hypothalamus, as well as suggested that nNOS could be a biomarker of the HPA axis linked to visceral hypersensitivity in IBS [20]. The experimental results discussed herein showed that nNOS protein and mRNA levels increased signi cantly in IBS rat with visceral hypersensitivity, which was also accompanied by the imbalance of gut microbiota, as demonstrated by an increase in the abundance of pathogenic bacteria, such as Escherichia coli, as well as a decrease in the proportion of obligatory anaerobic bacteria, including butyrate-producing bacteria.…”
Section: Discussionmentioning
confidence: 99%